EVALUATION OF COLD RESISTANCE AND SELECTION OF CHILL-PROOF MEASURE OF THREE PHLOX CULTIVARS - X. Han; B. Han (Journal of Animal and Plant Sciences, 2015)
In this study, Phlox paniculata cultivars ‘Aida,’ ‘Purpurea,’ and ‘Rosea’ were investigated in a cold resistance experiment. Relative electrical conductivity, soluble sugar content, and free proline content were selected as physiological targets, and the states of growth of the three Phlox cultivars under cold stress were observed after a year. Results showed that P. paniculata ‘Purpurea’ was more tolerant to cold than the two other cultivars. Earth covering, use of straw curtains, and frost-proof water were used as chill-proof measures in winter, and field conditions were analyzed for comparison. The most feasible chill-proof measure for the three Phlox cultivars was found to be earth covering. Overall, this study plays an important role in the introduction of Phlox species in Northern China.
Keywords: Phlox paniculata; cold resistant; relative electrical conductivity; soluble sugar content; proline content